Mastering Central Bank Communication Challenges via Twitter - Iikka Korhonen; Elisa Newby (Bank of Finland, 2019)
This study examines the Twitter policies and use of European central banks. Almost every European central bank maintains an institutional Twitter account, but tweeting activity, tweet content and usage restrictions on Twitter use by individual staff members vary considerably. We further consider the evolution of Twitter use by European central banks in light of the growing importance of financial stability in central bank policy messaging. To study these issues, we create a database of tweets from European central banks and financial supervisors, as well as attempt to gauge how closely professional economists follow central banks on Twitter. Central banks' Twitter activity has no relation to citizens' online participation. We also find that central banks' communication on financial stability with Twitter has increased over time, especially in comparison with monetary policy.
URN:NBN:fi:bof-201912201723
Keywords: E0; E5; E52; E58; G28; 330; central bank communication; monetary policy; financial stability; Twitter